Designing an Assessment Model for Teaching in Vocational Undergraduate Colleges in China - Xiaodong, Xue; Choeybal , Panayuth; Kunagornpitak, Praporntip (Journal of Roi Kaensarn Academi, 2024)
The purposes of this research were: 1) to investigate the components and indicators of teaching assessment for vocational undergraduate colleges, 2) to explore the actual state, expected state, and Priority Need Index of teaching assessment for vocational undergraduate colleges, 3) to design the teaching assessment model for vocational undergraduate colleges, and 4) to assess the suitability and feasibility of teaching assessment model for vocational undergraduate colleges. This study used mixed methods including literature review, expert interviews, questionnaires, data analysis, and connoisseurship. Questionnaire was developed with a sample of 378 teachers from 33 vocational undergraduate colleges in China, and the sampling survey method was used to understand the current state and expected state of vocational undergraduate colleges. The findings of this study were as follows: 1. The teaching assessment of vocational undergraduate colleges contains 6 components and 29 indicators. 2.The actual state and expected state of the components and indicators for vocational undergraduate colleges were at the high level. The needs of the components from high to low were: teaching construction and reform teaching faculty, teaching quality management, teaching conditions and utilization, teaching effect, and vocational skills accumulation. 3. Teaching assessment model for vocational undergraduate colleges was comprised. The teaching assessment model for vocational undergraduate colleges, including the assessment concept, assessment subjects, assessment contents, assessment methods, and application of assessment results. 4. The suitability and feasibility of the teaching assessment model for vocational undergraduate colleges were at the very high level.